The Analysis Of The Quality Of Family Planning (Kb) Health Services On Children's Nutritional Status At Sigambal Public Health Center, Rantau Selatan District, Labuhanbatu Regency - Ritonga, Tintin Insani Hartuti; Karnirius Harefa (Fakultas Kesehatan Masyarakat Institut Kesehatan Medistra Lubuk Pakam, 2024)
Background: Family planning services play an important role in supporting reproductive health and family well-being, especially in ensuring adequate nutrition for children. Objectives: to investigate the relationship between the quality of family planning (FP) health services and children's nutritional status at the Sigambal Health Center, Rantau Selatan District, Labuhanbatu Regency. Research method: structured interviews with mothers who participated in the family planning program and anthropometric measurements of their children.Results: there was a significant relationship between the quality of family planning services and children's nutritional status. High-quality family planning services have a positive impact on children's nutritional outcomes, as evidenced by improvements in weight and height indicators according to WHO standards. Factors determining service quality include the availability of contraception, the expertise of health workers, and community involvement in family planning initiatives.Conclusion: This study emphasizes the importance of improving family planning services by ensuring adequate resources, ongoing training for health personnel, and encouraging community participation. These efforts are critical to improving children's nutritional status in the region